2015
DOI: 10.5336/nurses.2014-42620
|View full text |Cite
|
Sign up to set email alerts
|

Women's Knowledge, Beliefs and Behaviors About Cervical Cancer and Pap Smear Test

Abstract: Ya zış ma Ad re si/Cor res pon den ce: Rabia HACIHASANOĞLU AŞILAR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Araştırma sonuçlarıyla benzer şekilde yapılan diğer araştırmalarda pap smear testi hakkında bilgisi olanların, pap smear testinin yapılma nedenini bilenlerin ve pap smear testini daha önce duyanların duyarlılık, sağlık motivasyonu ve pap smear yarar/sağlık motivasyonu algılarının yüksek, pap smear engel algılarının düşük olduğu bulunmuştur. (5,14,15,29,30). Çalışma sonuçlarında da görüldüğü gibi pap smear testi hakkında bilgi düzeyi ve testi duyma oranı arttıkça, serviks kanseri ve pap smear testi ile ilgili sağlık inançlarının olumlu olarak arttığı görülmektedir.…”
Section: Rahim Ağzı Kanseri Ve Pap Smear Testi Sağlık İnanç Modeli öLçeğiunclassified
“…Araştırma sonuçlarıyla benzer şekilde yapılan diğer araştırmalarda pap smear testi hakkında bilgisi olanların, pap smear testinin yapılma nedenini bilenlerin ve pap smear testini daha önce duyanların duyarlılık, sağlık motivasyonu ve pap smear yarar/sağlık motivasyonu algılarının yüksek, pap smear engel algılarının düşük olduğu bulunmuştur. (5,14,15,29,30). Çalışma sonuçlarında da görüldüğü gibi pap smear testi hakkında bilgi düzeyi ve testi duyma oranı arttıkça, serviks kanseri ve pap smear testi ile ilgili sağlık inançlarının olumlu olarak arttığı görülmektedir.…”
Section: Rahim Ağzı Kanseri Ve Pap Smear Testi Sağlık İnanç Modeli öLçeğiunclassified
“…12 In the studies conducted in Turkey, it has been reported that women have never undergone CC screening tests in diff erent rates (32.4%, 44.1%, and 82.8%). 13 Th is study was conducted to determine health belief levels of women who were living in a city center and applied to KETEM towards cervical cancer and pap smear tests and identify if the sociodemographic characteristics make a diff erence or not.…”
Section: Screenings For Cervical Cancer In Turkey Are Carried Out Bymentioning
confidence: 99%
“…In the collection of the data, Personal Information Form was developed by the researchers upon the literature review. [13][14][15][16] Th is form is composed of a total of 13 questions containing information about sociodemographic characteristics of the mothers (9 questions), HPV, pap smear test and cervical cancer (4 questions).…”
Section: Population and Sample Of The Studymentioning
confidence: 99%